Punishment in criminal law means of personal liberty - Авдеев, Вадим Авдеевич; Авдеева, Екатерина Вадимовна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
A study of the sanctions of criminal law regulating the mechanism of criminal law protection of individual freedom by the example of art. 126-128 of the Criminal Code, has allowed to establish the following trends. The position of the legislator on registration of sanctions under consideration norms reflected in the penalties and other measures of criminal law, appointed by the courts for infringement on personal freedom. The proportion of those convicted of crimes against individual freedom in 2014 was as follows: for kidnapping - 59.4%, false imprisonment - 34.0%, trafficking in human beings - 4.2%, the use of slave labor - 2.2% and illegal hospitalization medical organization for the provision of psychiatric care in a hospital - 0.2%. The vast majority of convictions includes a reference to imprisonment for a certain period of time (61.3%) or a conditional sentence to imprisonment (30.9%). The following items in this list takes restraint (5.7%). Lower rates are typical for these types of punishment as a corrective work (0.5%) and fine (0.3%). In 2015 (January-June), the proportion of those convicted of crimes against the freedom of the individual has made: for kidnapping - 58.2%, false imprisonment - 34.4%, trafficking in human beings - 6.3%, the use of slave labor - 1 1% and nezakonnuyugospitalizatsiyu in the medical organization to provide assistance psihiatricheskicheskoy in stationary conditions - 0.0%. The vast majority of convictions includes a reference to imprisonment for a certain period of time (67.8%) or a conditional sentence to imprisonment (21.5%). The following items in this list takes restraint (2.6%). Lower rates are typical for these types of punishments like community service (1.1%) and correctional work (0.7%). Priority position among the forms of realization of criminal responsibility remains with the deprivation of liberty for a certain period of time. So, more than half of the number of those sentenced to imprisonment were convicted for a period of more than five years (50.4%). Sentenced to a term of three to five years in prison subject to one in five (27.9%) committed a crime against the freedom of the individual. Minimum sentences were appointed little group of prisoners. In particular, 13.3% of the prisoners were sentenced to a term of two to three years. The term of up to one year has been assigned 4.5% of the convicts, and more than one year up to two years - 3.9% of the convicts. Imprisonment for a certain term was imposed for kidnapping depending on the presence or absence of aggravating circumstances in the following ratio: Part 1 of Art..126 of the Criminal Code of the Russian Federation - 35.9%; h. 2 tablespoons. 126 of the Criminal Code of the Russian Federation - 76.4%; h. 3 tbsp. 126 of the Criminal Code of the Russian Federation - 87.5%. The following indicators of deprivation of liberty for the purpose characteristic convicted of unlawful confinement: Part 1 of Art..127 of the Criminal Code of the Russian Federation - 14.5%; h. 2 tablespoons. 127 of the Criminal Code of the Russian Federation - 30.3%; h. 3 tbsp. 127 of the Criminal Code of the Russian Federation - 45.5%. The dominant form of punishment for trafficking is imprisonment for a fixed term, appeared in the 60% penalty on the hour. 1, Art.Of the Criminal Code in 1271, 78.9% of sentences for hours.2, Art. 1271 Criminal Code of the Russian Federation and 80% of convictions for h. 3 tbsp. 1271 Criminal Code. The use of slave labor under Part. 1, 2 tbsp. 1272 of the Criminal Code, entailed the appointment of probation to imprisonment (20%) and imprisonment for a specified period (80%). Criminal liability for illegal placement in a psychiatric hospital under Part. 2 tbsp. 128 of the Criminal Code, entailed the conditional sentence to imprisonment only convict. Convicted of kidnapping, based on the categories of offenses, mainly to impose penalties of imprisonment (73.9%). Probation appeared in 26.1% of guilty verdicts in courts investigated category of cases. Implementation of the criminal liability of individualization and differentiation principles promotes differentiation of penalties and other measures of criminal law, including accomplices in a criminal case. However, the approach of law enforcement changed in criminal cases, paired with a charge of false imprisonment. The actual serving of the sentence of imprisonment was imposed for each convict fourth (26.6%). courts Preference was given a suspended conviction (56.1%). Indicators sentenced to restriction of freedom for the false imprisonment meet 14.9%. Comparative analysis of the proportion of persons sentenced to probation and actual penitentiary reveals the following patterns. Thus, 55% of those found guilty of committing crimes under Art. 126, 127 of the Criminal Code, were sentenced to imprisonment for a fixed term. According to Art.1271, 1272 of the Criminal Code to imprisonment for a certain period subject to the condemnation of 76.5%. Thus the optimization of the criminal law protection of individual liberty implies the improvement of punishment and other measures of criminal law, the implementation of the functions and purposes of criminal law on convicts resocialization and social adaptation. Ensuring freedom of the individual in the Russian Federation by means of criminal law requires the use of new approaches to enforcement activities implemented in the context of crime prevention and stimulation of post-positive behavior.